2012
DOI: 10.2478/v10175-012-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable structure electronic commutator for a dual BLDC motor EV drive

Abstract: Abstract. An electronic commutator that can drive a PM BLDC motor either in the full bridge or half bridge configuration has been developed. This commutator allows increasing the motor speed over the nominal value, hence the motor is able to operate within a wide constant power speed range. An application of the commutator with a reconfigurable structure for the double drive of a small electric vehicle Elipsa has been presented. The driveline consists of two independent commutators feeding the motors coupled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was shown that this difficulty could be eliminated by appropriate switching of the modes of converter's transistors control in a cycle: braking→motor's work→braking. The solutions of both problems were registered for patent protection [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that this difficulty could be eliminated by appropriate switching of the modes of converter's transistors control in a cycle: braking→motor's work→braking. The solutions of both problems were registered for patent protection [13].…”
Section: Discussionmentioning
confidence: 99%
“…To counteract this phenomenon, it was proposed to control the commutator's switches in a way enabling work with electric braking [13]. This method requires the braking operation mode and motor operation mode to be periodically switched over.…”
Section: Ev Drive Systemmentioning
confidence: 99%
“…However, this method necessitates additional sources selection switches, an electronic gearshift, and requires access to the different connection of the motor winding. An electronic commutator based on a reconfigurable structure of the BLDC motor inverter is presented in Biskup et al 14 Additional switches are added to achieve higher speed operation. Nonetheless, this structure needs the motor neutral connection, which is not always easy to access.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are commonly applied in military, industrial and domestic equipment. Modern PM motors usually cooperate with different type of power converters to obtain high efficiency across a wide range of electromechanical characteristics [1][2][3][4][5][6][7][8]. The full-bridge controlled converter is a widely used solution for PM motors which associate two other phases with the highest instantaneous value of back EMF voltages [9].…”
Section: Introductionmentioning
confidence: 99%